Educational Leadership and Policy for Sustainable Development Goals (SDGs) - Carlo Mende; Fatim Zumaro (Innovative Journal of Educational Research and Insights, 2025)
This study investigates the interlanguage patterns in the written Arabic of non-native speakers by employing an error analysis approach. The research aims to identify the most frequent types of linguistic errors, analyze their underlying causes, and discuss the implications for Arabic language teaching and learning. Data were collected from student compositions and analyzed based on grammatical, lexical, and orthographic aspects. The findings reveal recurring patterns of interlanguage influenced by the learners’ first language and limited exposure to authentic Arabic texts. Moreover, the analysis highlights that fossilization and transfer errors are dominant in shaping learners’ interlanguage system. These insights provide valuable input for educators in designing more effective pedagogical strategies to address learners’ difficulties in mastering standard written Arabic. Ultimately, this study contributes to a better understanding of second language acquisition processes and offers practical recommendations for improving Arabic language instruction